2019
DOI: 10.1007/s10461-019-02452-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Mobile Health Intervention to Promote HIV Self-testing with MSM in China: A Randomized Controlled Trial

Abstract: This study tested a mobile health (mHealth) intervention program entitled WeTest, delivered via the WeChat mobile app, to promote oral HIVST among MSM in Hefei, China. A total of 100 MSM participants enrolled, completed baseline assessment, were randomly assigned to intervention or control, and completed 6-month follow-up surveys. Intervention participants (n=50) received two oral HIVST kits and access to WeTest, a private WeChat group which provided app-based messages and referrals to health services related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(114 citation statements)
references
References 32 publications
(34 reference statements)
3
98
0
1
Order By: Relevance
“…Our results showed that HIVST Users had a higher frequency of gay apps use than Non-HIVST users in the prior 6 months. As with previous ndings, the utility of mobile health interventions can engage MSM in HIVST in Heifei and Shenzhen, China 27,28 , and increase rates of con rmed HIV diagnoses and linkage to clinical care in the UK 29 . Furthermore, consistent with ndings in other studies 22 , those who had high-risk sex behavior, including multiple male sex partners, frequency of male-male sexual contact more than once per week and syphilis infection were more likely to have had HIVST.…”
Section: Discussionsupporting
confidence: 65%
“…Our results showed that HIVST Users had a higher frequency of gay apps use than Non-HIVST users in the prior 6 months. As with previous ndings, the utility of mobile health interventions can engage MSM in HIVST in Heifei and Shenzhen, China 27,28 , and increase rates of con rmed HIV diagnoses and linkage to clinical care in the UK 29 . Furthermore, consistent with ndings in other studies 22 , those who had high-risk sex behavior, including multiple male sex partners, frequency of male-male sexual contact more than once per week and syphilis infection were more likely to have had HIVST.…”
Section: Discussionsupporting
confidence: 65%
“…The length of follow-up ranged from immediate after intervention [61] to 12 months [49,58,[62][63][64] with the average retention rate of 79.8% (ranging from 46.0 [65] to 100% [66][67][68][69]). Four studies measured pre and post-evaluations in different participants [70][71][72][73].…”
Section: Length Of Follow-up and Retention Ratementioning
confidence: 99%
“…Two studies using smartphone applications (apps) are pilot RCTs [57,68], and one study was pilot pre-post experiment [78]. Bauermeister et al developed an application with six sessions based on the Dual Processing Cognitive-Emotional Decision-Making Framework [57].…”
Section: Smartphone Applications (N = 3)mentioning
confidence: 99%
See 2 more Smart Citations